Made in Chinatown : Chinese Australian Furniture Factories, 1880-1930 - Gibson, Peter Charles (Sydney University Press, 2022)
Made in Chinatown delves into a little-known aspect of Australia's past: its hundreds of Chinese furniture factories. These businesses thrived in the post-gold rush era, becoming an important economic activity for Chinese immigrants and their descendants and a vital part of Australia's furniture industry. Yet, owing to an exclusionary vision for Australia as a bastion of 'white' industry and labour, these factories were targeted by anti-Chinese political campaigns and legislative restrictions. Guided by Chinese manufacturers' and workers' own reflections and records, this book examines how these factories operated under the exclusionary vision of White Australia. Historian Peter Gibson uses previously untapped archival sources to investigate the local and international factors that boosted the industry, and the business and labour practices associated with factory operation. He explores the strategies employed in efforts to resist injustice, and the place of Chinese furniture factories within the contexts of Australian enterprise, work and consumerism more broadly. Made in Chinatown argues that Chinese Australian furniture manufacturers and their employees were far more adaptable, and the White Australia vision less pervasive, than most histories would suggest. - Publisher's description.
Keywords: Furniture industry and trade -- Australia -- History.; Furniture making -- Australia -- History.; Chinese -- Australia -- History.; Cabinetmakers -- Australia -- History.; Furniture workers -- Australia -- History.; Meubles -- Industrie -- Australie -- Histoire.; Meubles -- Fabrication -- Australie -- Histoire.; Chinois -- Australie -- Histoire.; Ébénistes -- Australie -- Histoire.; Menuisiers en meubles -- Australie -- Histoire.; Cabinetmakers; Chinese; Furniture industry and trade; Furniture making; Furniture workers; Australia; History